2009
DOI: 10.1590/s1516-89132009000600029
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of oil refinery residues using mixed-culture of microorganisms isolated from a landfarming

Abstract: In this study, the potential for using an inoculum composed of a mixed-culture of bacteria and fungi, isolated from a landfarming at the Paulínia Oil Refinery, Brazil, to degrade oil residues generated in the process of petroleum refinement was investigated. The isolation of these microorganisms was carried out beforehand, assuming that they would be better adapted to petroleum hydrocarbons, as the landfarming consisted of an area impacted by the deposit of such compounds. The Bartha and Pramer respirometric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…These results agree with other studies [26][27][28][29]. Sunita et al [29] reported faster utilization of hydrocarbon by mixed cultures than the individual bacterial strain .The phenomenon was explained by Venosa and Zhu [27], who assumed that there is no single strain with the metabolic capacity to degrade all components found within crude oil.…”
Section: Biodegradation Of Crude Oil By Batch Cultivation Of Individusupporting
confidence: 91%
“…These results agree with other studies [26][27][28][29]. Sunita et al [29] reported faster utilization of hydrocarbon by mixed cultures than the individual bacterial strain .The phenomenon was explained by Venosa and Zhu [27], who assumed that there is no single strain with the metabolic capacity to degrade all components found within crude oil.…”
Section: Biodegradation Of Crude Oil By Batch Cultivation Of Individusupporting
confidence: 91%
“…Stenotrophomonas also had been isolated from petroleum and refinery site and was confirmed of its ability to degrade Methyl tert-butyl ether (MTBE)-contaminated water [31]. Furthermore, Stenotrophomonas maltophilia was also being used together with other bacteria in biodegradation of oil residues from petroleum refinement and other bioremediation and phytoremediation studies [32,33].…”
Section: Discussionmentioning
confidence: 97%
“…Microorganisms are considered efficient biodegradation promoters, because of its abundance, diversity of species and catabolic and anabolic versatilities, as well as its capacity of adaptation to adverse environmental conditions (Moraes and Tornisielo, 2009). Several metabolic pathways of degradation of PHA's have been identified in various microorganisms.…”
Section: Bioremediationmentioning
confidence: 99%